Faktor Penentu Green Marketing Mix Decision pada Coffee Shop di Yogyakarta - Nia Kartika Putri; Gia Rizky (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
The increasing volume of waste, particularly food waste and plastic waste, has become an important environmental issue in Yogyakarta. The rapid growth of coffee shops in Yogyakarta has intensified business competition. To address these challenges, companies have implemented green marketing mix as a differentiation strategy. This study aimed to analyze the influence of managerial commitment, green orientation, green innovation capability, and green brand image on green marketing mix decision among coffee shops in Yogyakarta. The research employed a quantitative approach using a non-probability sampling technique through the convenience sampling method. Data were collected from 109 coffee shop management representatives and were analyzed using logistic regression. The results showed that green orientation had a significant positive influence on green marketing mix decision. In contrast, managerial commitment, green innovation capability, and green brand image did not have a significant influence on green marketing mix decision. However, all independent variables simultaneously influenced green marketing mix decision. The study concluded that green orientation was the most influential factor in determining green marketing mix decision among coffee shops in Yogyakarta. Therefore, coffee shop management should strengthen environmental orientation as a basis for strategic decision-making to support the successful implementation of green marketing mix practices.